Analisis Vegetasi di Habitat Orangutan, Stasiun Penelitian Ketambe, Taman Nasional Gunung Leuser, Aceh Tenggara - Ike Nayasilana; Utami Atmoko; N. Andayani (Biology Department, Faculty of Science and Technology, Univeristas Jambi, Indonesia, 2015)
Orangutans occur in both primary and ex-logged forests of Ketambe Research station, Gunung Leuser National Park, Aceh. Vegetation analysis was carried out to compare the two habitat types, as a basis to understand the ecology of orangutans in disturbed habitats. Data on 20 plots vegetation analysis 25x25 m (Juli 2010). The study recorded 275 trees from 99 species in the primary forest (67 species are food fruit trees), while the ex-logged forest contains 303 trees from 87 species (56 species are food fruit trees). Although the ex-logged forest still has pioneer species, such as Elateriospermum tapos and Macaranga sp., the two habitat types are not too dissimilar as shown by a relatively high index similarity (ISs = 59,70% for tree and 61% for liana). Diversity index (H’) of primary forest is also only slightly higher than of ex-logged forest (3,074 versus 2,961). These results indicate that natural succession during the last 8 years hasbeen going relatively well.